End of moderation: the radicalization of AKP in Turkey. Issue 7 (3rd October 2018) - Bashirov, Galib; Lancaster, Caroline
ABSTRACT: Turkey's Justice and Development Party, AKP, was for many years believed to be paramount in ushering in a new era of moderate Islamism. However, in recent years, AKP has troublingly reversed course. From violent repression of the Gezi protests of 2013 to the 2016 abortive coup and subsequent crackdown on opposition, the party has lost all semblance of moderate Islamism and radicalized. If AKP had truly moderated, how could the party have changed in such a short period of time? What explains the radicalization of AKP? First, we argue that the strategic benefits of moderation far outweighed its costs, rendering it analytically improbable to determine whether AKP's actions were genuine or merely strategic. Second, we show that AKP has been in a process of radicalization characterized by the adoption of anti-system, anti-democratic, and violent tactics and rhetoric since 2011. The disappearance of domestic and international structural constraints created the requisite background conditions for the party's radicalization. Radicalization was facilitated by what we call 'Erdoganization', an ongoing de-institutionalization process within which Tayyip Erdogan gained complete control over the party. Additionally, a series of four "external shocks" threatened the party's primary goal of gaining hegemony and caused the party to radicalize.